HUBUNGAN DAN PENGARUH AKTIVITAS SUNSPOT TERHADAP DINAMIKA KEJADIAN PETIR : (STUDI KASUS AKTIVITAS PETIR DI KOTA TERNATE DAN SEKITARNYA) - Sabila, Wildan Ichsan (Jurnal Widya Climago, 2024)
The relationship and influence between lightning activity and sunspot activity are relevant in understanding potentially hazardous and detrimental natural phenomena. This research aims to determine the relationship and influence of sunspot activity on lightning activity in the area of Kota Ternate and its surroundings. The study utilizes lightning and sunspot data spanning a period of 13 years in the Ternate city area and its vicinity. The results of the analysis indicate a positive correlation, but not very strong. Regression analysis shows that sunspot activity influences lightning activity by 47.5%. Trend analysis reveals that the majority of lightning occurrences follow the trend of sunspot activity. This indicates a relationship and influence between lightning activity and sunspot activity. With a deeper understanding of the factors influencing lightning activity, we can develop more effective mitigation strategies and increase awareness of the potential hazards associated with lightning